Analisis Manajemen Pembelajaran Diferensiasi Dalam Penguatan Profil Pelajar Pancasila Melalui Mata Pelajaran IPS di SMAN 2 Sampit - krisma natalia (Satya Sastraharing : Jurnal Manajemen, 2023)
A student profile based on Pancasila is a characteristic that must be formed and realized by students when implementing the independent curriculum. This research was conducted at SMAN 2 Sampit, East Kotawaringin Regency, in 2022, which has independently implemented the independent curriculum. The aim of this research is to identify the implementation of differentiated learning in social studies subjects, as well as identify the obstacles and factors that encourage the implementation of differentiated learning in schools. This research is qualitative in nature and uses data collection methods through observation, documentation and interviews. The research results show that differentiated learning in social studies subjects is carried out through differentiation in processes, content and products, in accordance with the principles of differentiated learning. However, differentiated learning in social studies subjects is still not implemented optimally, because teachers experience difficulties in implementing it. Teachers still have difficulty in preparing teaching modules that are suitable for differentiated learning and managing classes according to the principles of differentiated learning. The factor that encourages the implementation of differentiated learning is the leadership of the school principal who provides motivation to teachers and organizes various training, seminars and workshops. Meanwhile, the factors that hinder the implementation of differentiated learning are the teacher's readiness in planning differentiated learning and the teacher's ability which is not yet optimal in carrying out diagnostic assessments and understanding the dimensions of student profiles based on Pancasila which will be developed in learning.